Nervous system–gut microbiota–immune system axis: future directions for preventing tumor - Wang, Juanjuan; Cheng, Wenyue; Yang, Rongcun (Frontiers in Immunology, 2025)
Tumor is one of the leading causes of death worldwide. The occurrence and development of tumors are related to multiple systems and factors such as the immune system, gut microbiota, and nervous system. The immune system plays a critical role in tumor development. Studies have also found that the gut microbiota can directly or indirectly affect tumorigenesis and tumor development. With increasing attention on the tumor microenvironment in recent years, the nervous system has emerged as a novel regulator of tumor development. Some tumor therapies based on the nervous system have also been tested in clinical trials. However, the nervous system can not only directly interact with tumor cells but also indirectly affect tumor development through the gut microbiota. The nervous system-mediated gut microbiota can regulate tumorigenesis, growth, invasion, and metastasis through the immune system. Here, we mainly explore the potential effects of the nervous system–gut microbiota–immune system axis on tumorigenesis and tumor development. The effects of the nervous system–gut microbiota–immune system axis on tumors involve the nervous system regulating immune cells through the gut microbiota, which can prevent tumor development. Meanwhile, the direct effects of the gut microbiota on tumors and the regulation of the immune system by the nervous system, which can affect tumor development, are also reviewed.